Risk communication to vulnerable populations on crimes in the Economic Community of West Africa: case-study of Ghana - Norman, Ishmael D.; Kpeglo, Emmanuel D.; Nadarajah, Saralees; Awiah-Norman, Blandina (Frontiers in Communication, 2025)
This research study examines how risk communications on personal and societal security are conducted within the Economic Community of West African States, using Ghana as a case study. The research focused on Ghana due to its status and ranking as a leading democratic and peaceful nation within a turbulent region, in comparison to Kenya, a member of the East African Community and the Southern African Development Community. In addition to field data, a literature review was conducted to examine whether Ghana’s national security agencies apply key risk communication components, such as risk identification, population impact assessment, communication effectiveness, mitigation strategies, and feedback mechanisms. Findings indicate that both national and regional frameworks for risk communication are largely absent, with existing protocols being mostly ad hoc and confined to health emergencies. Although the states and citizens in the West African region are aware of crimes, these states often employ ad hoc risk communication strategies to address interpersonal crimes. The analysis used data to assess individuals’ self-efficacy in taking personal preventive measures in relation to their perceived ontological security over the same crimes. Age-based differences in perceived crime threats were statistically significant for rape, kidnapping, defilement, and murder (Kruskal–Wallis p < 0.01). The study concludes that there are few or no national or regional risk communication modalities to prepare both the capable and vulnerable populations against interpersonal crimes, terrorism, or insurgency. The study recommends that the Joint Security Committee of Ghana and other nations in the region develop an All-Risk Communication protocol for national application to improve safety and national response capabilities. The research contributes to knowledge on systems risk communication and creates awareness of the need for nations to develop national protocols for risk communication to assist first responders in their performative service deliveries.